EVALUATION OF KNOWLEDGE BEFORE AND AFTER HEALTH EDUCATION ON ACUTE HEPATITIS IN CHILDREN AT TAMAN BACAAN PUBLIC HEALTH CENTER - Muhammad Aziz; Sylvia Sylvia; Stephanie Siahaan (Majalah Kedokteran Sriwijaya, 2022)
Hepatitis is the process of inflammation and/or necrosis of liver tissue. Infectious hepatitis is the most common cause of acute hepatitis. This study aimed to examine the level of public knowledge about hepatitis in children before and after being given health education at the Taman Bacaan Public Health Center. This study used descriptive research method, seeking and collecting data in the field with the aim of knowing the level of public knowledge before and after being given health education about hepatitis in children. This study involved 96 respondents. The descriptive analysis results showed that most respondents were between 20 to 35 years old and female. Most of the respondents had good knowledge about hepatitis before given the health education about hepatitis in children. Most of the respondents had good attitude and high interest in preventing hepatitis.  The bivariate analysis results in this study that there is an effect of providing health education about hepatitis in children to the community (T value = 17.04). Education still needs to be continued because the most important goal of health education is to achieve changes in individual, family and community behavior in maintaining clean living behaviors and a healthy environment, as well as playing an active role in efforts to achieve optimal health status.